Physico-chemical analysis of control and optimized ‘Banana Enriched Ice Cream’ during storage period (60 days) at 15 days intervals - ., Saloni; Rai, D C; Rai, Himanshu Kumar; Kumar, Vikash (Indian Journal of Dairy Science, 2020)
Ice cream is a frozen product and the popularity of ice cream and frozen desserts is attributed to their refreshingly cool and delightfully sweet characteristics. The present research work was conducted to study the effect of storage periods on different physico-chemical properties of optimized (banana pulp enriched ice cream) and control ice cream. The storage study was done at 15 days interval up to 60 days. On the basis of findings, it was observed that the overrun, hardness, first dripping time, melting rate, complete melting time and fat were significantly (P<0.05) changed over the storage period but total solids, protein and titrable acidity content of optimized and control ice creams did not differ significantly throughout the storage period. The physico-chemical composition of optimized ice cream observed were 36.57% total solids, 8.66 % fat, 4.15 % protein, 0.22% acidity and 48.50% overrun and of control ice cream observed were 36.48% total solids, 9.86% fat, 4.45% protein, 0.22% acidity and 44.69% overrun.